pH responsive polymers with amino acids in the side chains and their potential applications - Roy, Saswati Ghosh; De, Priyadarsi (Journal of applied polymer science, 2014)
ABSTRACT Design and synthesis of pH responsive polymeric materials has become an important subject in academia as well as in industrial field in recent years due to their applications in diverse field including controlled drug delivery, biomedical applications, membrane science, sensors and actuators, oil recovery, colloid stabilization, etc. Efforts have been made to incorporate stimuli‐responsive biomolecules in synthetic polymers to develop pH responsive “smart” non‐biological hybrid macromolecules with high water solubility, enhanced biocompatibility, bio‐mimetic structure and properties. This review is focused on the recent advances in side‐chain amino acid‐based pH responsive polymers synthesis and potential application aspects of these macromolecular architectures in drug and gene delivery, and other fields. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 41084.